ANALISIS PARTISIPASI MASYARAKAT DALAM PENGELOLAAN RUANG TERBUKA HIJAU (RTH) PUBLIK DI KECAMATAN JEBRES KOTA SURAKARTA TAHUN 2022 - Indrajati, Efi; Sugiyanto; Prihadi, Singgih (INDONESIAN JOURNAL OF ENVIRONMENT AND DISASTER, 2023)
This research was conducted to determine the availability and adequacy of Public Green Open Spaces (RTH) and determine community participation in the management of Public Green Open Spaces (RTH). The research method used in this research is descriptive qualitative method with a spatial approach. The population in this study were public green open space, managers and the community living around the research location in Jebres District. The sampling technique in this study used the incidental sampling technique. The results of the study show Availability and Adequacy of Public Green Open Space (RTH) (a) Availability of Public Green Open Space (RTH) in Jebres District as many as 170 points with an area of 146.10 ha. With categories in the form of Green Open Space for Parks and City Forests, Green Open Green Roads and Certain Green Open Space. (b) The adequacy of public green space in Jebres District according to Minister of Public Works Regulation No. 05/PRT/M/2008 is 287.6 ha. While the availability value of Public Green Open Space (RTH) is 146.1 ha or 10.16%. So, Jebres District has a deficiency of 141.5 ha or 9.84%. In addition, Community Participation (a) The level of community participation in Jebres District in 2022 is Therapy with a score of 16.07; Information with a score range of 33.93-34.97; Consultation with a score range of 38.10-47.32; Placement with a score range of 52.96-59.82; Delegates Power with a score of 80.36. (b) The stages of community participation in Jebres District in 2022 are; Participation in Implementation with a score range of 43.75-48.44%; Participation in Benefit with a score range of 53.91-72.92%; Participation in Evaluation with a score of 81.25%. (c) Factors that influence the level and stages of community participation in Jebres District in 2022 with a total of 100 respondents.